2021
DOI: 10.1097/01.hjh.0000748876.14218.2b
|View full text |Cite
|
Sign up to set email alerts
|

A Cross Sectional Observational Study Evalating Perspectives and Therapeutic Options Amongst Clinicians in Young Indian Hypertensives

Abstract: Objective: Hypertension has been reported in 12.1% of young adults in a recent population-based study in India and is a growing concern. There is a paucity in guidelines on the definite therapeutic approach in young hypertensives. This study aimed to understand the clinician's perspective on approach to management of hypertension in young adults in India. Design and method: Cross-sectional observational survey conducted between February 6, 2020 and 22 F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Telmisartan and metoprolol single-pill combination achieved the blood pressure target in 40%-60% of patients as reported by 41.3% of the physicians. 14 The combination therapy was well tolerated in young hypertensive patients. Initiation of an early and appropriate antihypertensive treatment in young population may lower the burden of CVD in this population.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…Telmisartan and metoprolol single-pill combination achieved the blood pressure target in 40%-60% of patients as reported by 41.3% of the physicians. 14 The combination therapy was well tolerated in young hypertensive patients. Initiation of an early and appropriate antihypertensive treatment in young population may lower the burden of CVD in this population.…”
Section: Discussionmentioning
confidence: 94%
“…A cross-sectional, observational survey conducted by Jadhav et al revealed that amongst the ARBs, telmisartan was the preferred ARB by >80% respondents, and metoprolol was the preferred beta-blocker by almost 64% respondents. 14 Based on the rationale of sympathetic overactivity, most clinicians choose a β-blocker as part of antihypertensive prescription in hypertensive adults.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations